Neuroprotective effect of Cerebralcare Granule after cerebral ischemia/reperfusion injury - Zhang, Xiao-xiao (Neural Regen Res, 2016)
Cerebralcare Granule (CG) improves cerebral microcirculation and relieves vasospasm, but studies investigating its therapeutic effect on cerebral ischemia/reperfusion injury are lacking. In the present study, we administered CG (0.3, 0.1 and 0.03 g/mL intragastrically) to rats for 7 consecutive days. We then performed transient occlusion of the middle cerebral artery, followed by reperfusion, and administered CG daily for a further 3 or 7 days. Compared with no treatment, high-dose CG markedly improved neurological function assessed using the Bederson and Garcia scales. At 3 days, animals in the high-dose CG group had smaller infarct volumes, greater interleukin-10 expression, and fewer interleukin-1β-immunoreactive cells than those in the untreated model group. Furthermore, at 7 days, high-dose CG-treated rats had more vascular endothelial growth factor-immunoreactive cells, elevated angiopoietin-1 and vascular endothelial growth factor expression, and improved blood coagulation and flow indices compared with untreated model animals. These results suggest that CG exerts specific neuroprotective effects against cerebral ischemia/reperfusion injury.